2016
DOI: 10.1016/j.bbapap.2015.04.010
|View full text |Cite
|
Sign up to set email alerts
|

The catalytic function of renalase: A decade of phantoms

Abstract: Ten years after the initial identification of human renalase the first genuinely catalytic substrates have been identified. Throughout the prior decade a consensus belief that renalase is produced predominantly by the kidney and catalytically oxidizes catecholamines in order to lower blood pressure and slow the heart has prevailed. This belief was, however, based on fundamentally flawed scientific observations that did not include control reactions to account for the well-known autoxidation of catecholamines i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
1
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 81 publications
0
23
1
8
Order By: Relevance
“…Whether renalase is an amine oxidase or not is presently debated. Aliverti and Moran et al [6,7,8] failed to demonstrate the catalytic activity of renalase, which is contradictory to the investigation reported by Xu et al [1]. Thus, additional evidence is needed to confirm whether renalase is an amine oxidase.…”
Section: Introductioncontrasting
confidence: 54%
“…Whether renalase is an amine oxidase or not is presently debated. Aliverti and Moran et al [6,7,8] failed to demonstrate the catalytic activity of renalase, which is contradictory to the investigation reported by Xu et al [1]. Thus, additional evidence is needed to confirm whether renalase is an amine oxidase.…”
Section: Introductioncontrasting
confidence: 54%
“…Wang et al [37] showed that renalase promoted cell survival and protected against renal ischaemia reperfusion injury in mice through the activation of intracellular signalling cascades, independent of its ability to degrade catecholamines. More recently, Moran et al [38] found that, in fact, renalase does bind to , and performs no catalyic transformation of A [39]. Quelhas-Santos et al [40] reported that renalase degrades catecholamines catalyzing the formation of aminochromes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently discovered as a new renal hormone, renalase -flavin adenine dinucleotide (FAD) -dependent amine oxidase [3,4,5], is secreted by the kidneys and can metabolize the circulating CA and possibly play an important role in the regulation of sympathetic tone and blood pressure. The concept that renalase might be involved in the regulation of blood pressure is supported by the fact that the inactivation of the RNLS gene in mice by homologous recombination is associated with an elevated blood pressure, and a sympathetic activity in the absence of other measurable changes in renal function [6,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Possible mechanisms of renalase action that would account for the decrease of blood pressure remain elusive [4][5][6]. Nevertheless, administration of recombinant human renalase lowered arterial pressure in Sprague-Dawley rats [1,7].…”
Section: Introductionmentioning
confidence: 99%
“…Renalase is a recently discovered secretory protein involved in regulation of blood pressure [1][2][3][4][5][6]. Possible mechanisms of renalase action that would account for the decrease of blood pressure remain elusive [4][5][6].…”
Section: Introductionmentioning
confidence: 99%